2018
DOI: 10.1002/ags3.12071
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in treatment for colorectal liver metastasis

Abstract: A major challenge for the management of colorectal liver metastasis (CRLM) is the multidisciplinary approach including surgery. Resection is the most important treatment strategy to prolong the survival of patients with colorectal cancer (CRC). Even when resection is not possible as a primary treatment, it may still be carried out for curative intent after effective chemotherapy. Therefore, resection should always be considered when conducting chemotherapy for CRLM. Neoadjuvant anti‐epidermal growth factor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…2,12 So, the utility of perioperative chemotherapy in patients with resectable CRLM is controversial and patient treatment varies substantially among institutions. 13 Turning to the details of the operation, R1 resection increases the risk of local recurrence and long-term survival. Previous studies showed advantage in OS 14,15 or DFS 16 with a negative margin of 1 cm or more over subcentimeter nega-tive margins; however, Pawlik et al reported using multicenter database that 557 patients were stratified with margin status into positive, negative 1 to 4 mm, 5 to 9 mm, and 1 cm or more.…”
Section: A Change In Surgical Indicationsmentioning
confidence: 99%
“…2,12 So, the utility of perioperative chemotherapy in patients with resectable CRLM is controversial and patient treatment varies substantially among institutions. 13 Turning to the details of the operation, R1 resection increases the risk of local recurrence and long-term survival. Previous studies showed advantage in OS 14,15 or DFS 16 with a negative margin of 1 cm or more over subcentimeter nega-tive margins; however, Pawlik et al reported using multicenter database that 557 patients were stratified with margin status into positive, negative 1 to 4 mm, 5 to 9 mm, and 1 cm or more.…”
Section: A Change In Surgical Indicationsmentioning
confidence: 99%
“…Hematogenous and lymphogenous metastasis-dominant CRC with highfrequency MSI (MSI-H) are reported to have poor prognosis. However, the validity as the prognostic factor of MMR is still to be confirmed, and it should thus be used cautiously [20,21].…”
Section: Prognostic Determinantsmentioning
confidence: 99%
“…On the other hand, it is also known that RAS and BRAF mutations are of prognostic and predictive value in mCRC [21]. The pathogenesis of CRC involves the accumulation of genetic and epigenetic modifications within pathways that regulate proliferation, apoptosis, and angiogenesis.…”
Section: Prognostic Determinantsmentioning
confidence: 99%
See 2 more Smart Citations